Analisis Dampak Manajemen Konflik Toxic Friendship Pada Santri di Pondok Pesantren Darul Arifin 2 - Zulfah, Rania Firdausiah; Fitriyah, Della Wahyu; Zuhro’ Fitriana, Ani Qotus (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2022)
Being born into social beings makes humans dependent on one another. Building a friendship is a must as a form of human truth as a social being. Sometimes friends come and go according to where and the conditions experienced. However, it is not uncommon for friendships to be successfully built over the years. This study aims to determine the impact of toxic friendship experienced by students at Darul Arifin 2 Islamic Boarding School in terms of mental aspects such as insecurity, crisis of trust, and depression. The research method used in this journal is descriptive qualitative method. Data collection techniques in this study used observation, interviews, and documentation methods. Based on the results of research from interviews with sources, the sources stated that toxic friendship actions at Darul Arifin Islamic Boarding School do exist, in the form of toxic friendship actions, namely, criticism, bullying, no empathy, and body shaming. The results of this study indicate the different conditions experienced by each student in responding to the stimulus given by toxic friendship. The toxic friendship behavior experienced by students of Darul Arifin 2 Islamic Boarding School is dominant in the form of criticism and lack of empathy, then the impact experienced is dominant in feeling insecure and low self-confidence.